Variant Anatomy of Hypoglossal Canal: An Osteological Study in North Indian Population - Yadav S; Pandey P; Pasricha N; Bhatnagar R (Academia Anatomica International, 2020)
Introduction: To assess the presence of duplicated hypoglossal canal. Subjects and Methods: A total of 80 dried human skulls were collected from the Anthropology lab of the department of Anatomy K.G.M.U.,U. P., Lucknow, India. The skulls were examined for duplicated hypoglossal canal and presence of posterior condylar canal. Theskulls were closely inspected with the use of hand lens. Results: We observed bilateral duplicated hypoglossal canal in 3 skulls (3.75%), Unilateral duplication was seen in 15 skulls (18.75%) [i.e.7 on the right side and 8 on the left side]. We observed that the presence of duplicated hypoglossal canal was mostly associated with the presence of posterior condylar canal. Conclusion: Duplicated hypoglossal canal in humans may result in minor degrees of alterations in the movements of the tongue due to entrapment of nerve during ossification. The clinical relevance of this knowledge is important for radiologists and neurosurgeons.